A novel distribution model of multiple teeth pits for evaluating time-varying mesh stiffness of external spur gears. (15th August 2019) - Chen, Taoyuan; Wang, Yanxue; Chen, Zhigang
Highlights: A new two-dimensional Gaussian distribution model is proposed to simulate pitting distribution. The overlaps of the pits and pits in the boundary of the tooth surface are also considered in the computation of TVMS. A new method has been proposed for calculating the TVMS of two meshing gears with multiple tooth pitting. Abstract: Tooth damage often causes gear mesh stiffness to decrease. Therefore, time-varying mesh stiffness (TVMS) can reflect the health condition of gears. A new two-dimensional Gaussian distribution model is proposed to simulate pitting distribution. In the initial stage, the pitting model is built with pits satisfying a predefined two-dimensional Gaussian distribution. With the development of pitting, both the diameter and the depth of pitting dents will increase, meanwhile new pits that satisfies another two-dimensional Gaussian distribution will be generated near the existing pitting area. The overlaps of the pits and pits in the boundary of the tooth surface are also considered in the computation of TVMS. In addition, a new method has been proposed for calculating the TVMS of two meshing gears with multiple tooth surface pitting. Finally, the influence of different pitting on the TVMS has been analyzed in detail by numerical experiments. The validity of the proposed new distribution model and the method for TVMS have been successfully verified compared with the finite element model.